Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off. Issue 7 (1st July 2013) - Altieri, Andrew H.; Bertness, Mark D.; Coverdale, Tyler C.; Axelman, Eric E.; Herrmann, Nicholas C.; Szathmary, P. Lauren
Abstract : Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.